2000
DOI: 10.1136/gut.46.1.127
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin plus isosorbide 5-mononitrate versus somatostatin in the control of acute gastro-oesophageal variceal bleeding: a double blind, randomised, placebo controlled clinical trial

Abstract: Background-Variceal bleeding is a severe complication of portal hypertension. Somatostatin reduces portal pressure by decreasing splanchnic blood flow, and nitrates by diminishing intrahepatic resistance. Experimental studies have shown that the combination of somatostatin and nitrates has an additive eVect in decreasing portal pressure. Aim-To compare the therapeutic efficacy of either intravenous infusion of somatostatin plus oral isosorbide 5-mononitrate or somatostatin alone in gastrooesophageal variceal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…A single-center, double-blind, placebo-controlled trial was conducted by Junquera et al [11] to compare the effectiveness of somatostatin infusion alone to that of somatostatin plus oral isosorbide 5-mononitrate. Sixty patients with bleeding from esophageal or gastric varices were randomly assigned to receive a somatostatin infusion (250 µg/h) plus oral isosorbide 5-mononitrate (40 mg/12 h) (group I) or somatostatin plus a placebo (group II) for 72 hours.…”
Section: Vasoactive Drugsmentioning
confidence: 99%
“…A single-center, double-blind, placebo-controlled trial was conducted by Junquera et al [11] to compare the effectiveness of somatostatin infusion alone to that of somatostatin plus oral isosorbide 5-mononitrate. Sixty patients with bleeding from esophageal or gastric varices were randomly assigned to receive a somatostatin infusion (250 µg/h) plus oral isosorbide 5-mononitrate (40 mg/12 h) (group I) or somatostatin plus a placebo (group II) for 72 hours.…”
Section: Vasoactive Drugsmentioning
confidence: 99%
“…[ 5 ] Impaired gastric accommodation mainly causes upper GI symptoms such as early satiety, bloating and abdominal pain, and it is more likely to occur in patients with functional dyspepsia, diabetes mellitus, and those who have undergone fundoplication, vagotomy, or subtotal gastrectomy. [ 6 ] It has been found that the change in gastric receptivity during a meal was more prominent in cirrhotic patients than in healthy controls. [ 7 ] However, gastrointestinal (GI) stimulation, especially gastric dilation following food intake, may also cause corresponding GI symptoms.…”
Section: Introductionmentioning
confidence: 99%